The Position of the Sale and Purchase Deed and Responsibilities of the Land Deed Official in the Dual Certificate Case - Wininda Clara Puspita; Hoesin, H. Siti Hajati (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2021)
Ownership of a plot of land in Indonesia requires the existence of a land certificate, in this case the prospective land owner are obliged to register land on the plot of land to be owned. However, in practice and implementation there are still many problems related to land rights that lead to disputes in the midst of Indonesian society, even though the land registration has been carried out in accordance with the provision of the legislation, such as the subject matter in this article where there is a overlapping certificate issuance of a plot of land where there was a dispute between Sa'diyah as the Plaintiff against the Head of the Central Lampung Regency Land Office as the Defendant regarding the issuance of a overlapping certificate on a plot of the Right Land Ownership which was settled through the Bandar Lampung State Administrative Court based on Decree No. 24/G/2017/ PTUN-BL. The results of the decision stated that the defendant was obliged to revoke or withdraw the certificate of ownership rights in the name of Mrs. A. Ruyanti and what was the role and responsibility of PPAT towards the evidence of the Deed of Sale and Purchase in the form of land and buildings with the same object. This type of research is normative juridical research in the form of descriptive analytical. In this case, the legal protection has been partially fulfilled, but the PPAT and the head of the land office in this case are still questioning the legality of carrying out the existing procedures related to the issuance of certificates and the issuance of Deed of Sale and Purchase for the same object. Key words: Double Certificate Issuance; Overlapping Certificate; Land Registration.